PERAN DINAS PARIWISATA DAN DESA ADAT DALAM MENEKAN TINDAKAN KRIMINALITAS DI WILAYAH DESA ADAT KUTA - Prihandani, Ni Komang; Yasintha, Putu Nomy; Putri Wirantari, I Dewa Ayu (CITIZEN CHARTER, 2019)
ABSTRACT Badung Regency tourist destination thatalways crowded with tourists, especially in Kuta. Traditional Village of Kuta, or simply Kuta, is most favorite destinations. However, in 2015-2018 there has also been increase the number of theft crime in Kuta so the Australian Embassy issued a Travel Advisory. The purposes of this study are to find out and analyze the role of the Tourism Government Official of Badung Regency and the Government of Kuta in minimizing the criminal acts using the role theory of Henry Mintzberg. The role namely Interpersonal Role, Informational Role, and Decisional Role. The results showed that the Tourism Government Official of Badung Regency did its role but not by optimally, while the Government of Kuta has carried out role optimally in minimizing the crime by installing 100 CCTVs, doing night patrols, the formation of SJBS, as well as the completion of Awig-Awig and Pararem. Keywords: Role Theory, Tourism Security, Traditional Village of Kuta